(untitled) (SAARC Journal of Agriculture, 2022)
A field experiment was conducted in Lalmai-Hill area of Cumilla with five high yielding varieties (HYV) of rice during Boro season (2018-2019) to evaluate their yield performance under different transplanting dates. Rice seedlings were transplanted on three different dates viz., January 15 (T1), January 30 (T2) and February 14 (T3). Five rice varieties viz., BRRI dhan67 (V1) BRRI dhan68 (V2), BRRI dhan74 (V3), BRRI dhan81 (V4) and BRRI dhan86 (V5) were transplanted. Results revealed that delaying of transplanting date decreased yield and return of Boro rice varieties. Transplanting of seedlings on February 14 decreased effective tiller hill–1, filled grain panicle–1, grain yield and biological yield by 13, 14, 24 and 9%, respectively, compared to seedlings transplanted on January 15. Significantly highest grain yield (5.95 t ha–1) and biological yield (14.33 t ha–1) were obtained from BRRI dhan74 compared with other varieties because of higher potential of its yield attributes. The highest grain yield (6.67 t ha–1) and return (Tk. 158,765 ha–1) were recorded from BRRI dhan74 when transplanted on January 15 as compared to other combinations. Transplanting of all other varieties on January 15 confirmed higher yield and yield return compared with delayed transplanted seedlings. SAARC J. Agric., 20(1): 143-155 (2022)